Relocating English Studies and SoTL in the Global South: Towards Decolonizing English and Critiquing the Coloniality of Language - Ndlangamandla, Sibusiso Clifford; Chaka, Chaka (Journal of Contemporary Issues in Education)

(untitled) (University of Alberta, 2022)
South Africa has policies and frameworks for curriculum design, transformation, and quality assurance in each public institution of higher education (HE). These policies influence the scholarship of teaching and learning (SoTL), particularly at the departmental and disciplinary levels of English Studies. Despite the policy narratives and rhetoric, English Studies still carries vestiges of colonialism and apartheid in South Africa. Similarly, in other disciplines, scholars in the Global South have highlighted coloniality, epistemicides, epistemic errors, and epistemic injustices, but not in a dual critique of SoTL and the English language. Hypercritical self-reflexivity by academics should be the norm in SoTL, and this should be linked to language-based curriculum reforms and module content designs. All of these self-reflexive efforts should foreground how the mission to transform and decolonize is entangled with Eurocentric paradigms of English language teaching. This paper characterizes the nexus between SoTL and the coloniality of language within South African higher education. It also discusses and critiques the nature of an English department in a post-apartheid and postcolonial South Africa. In addition, it critiques the coloniality of language and imperial English language paradigms often embraced by higher education institutions (HEIs) in South Africa, and delineates curriculum transformation, Africanization, and decolonizing English within this educational sector. Finally, the paper challenges Eurocentric SoTL practices and colonialist English language paradigms by framing its argument within a critical southern decolonial perspective and a post-Eurocentric SoTL.